Metabolomics and its role in plant pathology - Bhatt, Bhagyashree; Shikha, Sneha; Mathpal, Sudha; Sharma, Geeta; Pandey, A. (Phytoprotection, 2022)
Metabolomics is one of the most eminent and newly emerging omic sciences. It is a powerful tool to study metabolic changes that occur in an organism. Plants produce a wide range of metabolites and the study of these metabolites can answer a number of questions that arise in the minds of researchers. Change in the metabolites is the most important feature in a genetically modified plant or plant interactions with pests, pathogens and the environment. Plant pathogen interactions are amongst the most biochemically complex mechanisms and pose a great challenge in front of plant pathologists; metabolomics not only play a great role in deciphering these complex interactions but also the study of certain defence-related metabolic changes can be utilized in a number of ways to protect the plant from the harmful pathogens. The science of metabolomics utilizes a number of techniques to study the wide variety of metabolites. This review will give a brief about the various techniques used in metabolomics and how some of these techniques have been successfully utilized in the field of plant pathology.